Muslim Entrepreneur Business Strategy in the Covid-19 Pandemic Era - Nur Kasanah; Ahmad Suminto (Institut Agama Islam Negeri Ponorogo, 2022)
The Covid-19 pandemic that has hit the whole world, including Indonesia, has changed people's habits and lifestyles. The implementation of social distancing, which requires people to maintain a safe distance, has a significant impact on business transactions both on a large industrial scale and entrepreneurial businesses. Many shopping centers are closed, market demand is declining, and business activities are no longer operating as usual. Indonesia, as a country with a majority Muslim population, needs Muslim entrepreneurs' role. In this situation, Muslim entrepreneurs need to rack their brains so that the business remains stable when demand declines. This article aims to analyze the business strategies carried out by Muslim entrepreneurs to survive and grow during this Covid-19 pandemic. This qualitative descriptive research methodology using a phenomenology approach shows the results that the efforts made include: believing the concept of work is worship and sustenance is a quota that must be picked up, innovating and diversifying products according to trends that are needed by the community, maintaining customer loyalty, being adaptive to technological developments and regulations, collaborating with third parties—and increasing social sensitivity through philanthropic activities, both donations and zakat, infaq, and alms so that the affected community can be helped and the economy will continue.Pandemi Covid-19 yang melanda seluruh dunia termasuk Indonesia merubah kebiasaan dan gaya hidup masyarakat. Penerapan social distancing yang mengharuskan masyarakat menjaga jarak aman, berimbas pada transaksi bisnis secara signifikan baik pada skala industi besar maupun usaha mandiri/ wirausaha. Banyak pusat perbelanjaan ditutup, permintaan pasar menurun dan aktivitas bisnis tidak lagi beroperasi seperti biasanya. Indonesia sebagai negara dengan mayoritas jumlah penduduk beragama Islam, tentu peran wirausaha muslim sangat dibutuhkan. Dalam situasi ini pelaku wirausaha muslim perlu memutar otak agar bisnis tetap stabil saat permintaan sedang menurun. Artikel ini bertujuan untuk menganalisis strategi bisnis yang dilakukan wirausahawan muslim untuk tetap bertahan dan bertumbuh di masa pandemi Covid-19 ini. Penelitian yang menggunakan metodologi penelitian kualitatif dengan pendekatan fenomenologi ini menunjukkan hasil penelitian bahwa upaya yang dilakukan antara lain: meyakini konsep kerja adalah ibadah dan rezeki adalah jatah yang harus dijemput, melakukan inovasi dan diversifikasi produk sesuai tren yang dibutuhkan masyarakat, menjaga loyalitas pelanggan, adaptif dengan perkembangan teknologi dan regulasi, melakukan kerjasama dengan pihak ketiga dan meningkatkan kepekaan sosial melalui kegiatan filantropi baik donasi maupun zakat, infak dan sedekah agar masyarakat terdampak bisa terbantu dan roda perekonomian tetap berjalan.